Characterization of a Granule-Bound Starch Synthase Isoform Found in the Pericarp of Wheat - Nakamura, Toshiki (American Society of Plant Physiologists, 1998)
Waxy wheat (Triticum aestivum L.) lacks the waxy protein, which is also known as granule-bound starch synthase I (GBSSI). The starch granules of waxy wheat endosperm and pollen do not contain amylose and therefore stain red-brown with iodine. However, we observed that starch from pericarp tissue of waxy wheat stained blue-black and contained amylose. Significantly higher starch synthase activity was detected in pericarp starch granules than in endosperm starch granules. A granule-bound protein that differed from GBSSI in molecular mass and isoelectric point was detected in the pericarp starch granules but not in granules from endosperm. This protein was designated GBSSII. The N-terminal amino acid sequence of GBSSII, although not identical to wheat GBSSI, showed strong homology to waxy proteins or GBSSIs of cereals and potato, and contained the motif KTGGL, which is the putative substrate-binding site of GBSSI of plants and of glycogen synthase of Escherichia coli. GBSSII cross-reacted specifically with antisera raised against potato and maize GBSSI. This study indicates that GBSSI and GBSSII are expressed in a tissue-specific manner in different organs, with GBSSII having an important function in amylose synthesis in the pericarp.